Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

NCAPG reprograms glycolytic and lipid metabolism by sustaining glycerophospholipid flux in small-cell lung cancer - Yang Sun; Jinglin Wen; Rui Su; Linlin Liu (Molecular and Cellular Biochemistry, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Genomic and functional characterization of a novel urease-producing bacterium Sulfitobacter sp. IGS-18 for simultaneous coal dust suppression and ammonia nitrogen removal during microbially induced calcite precipitation - Wen Nie; Ruoxi Li; Yue Zhao; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Coupling MICP with hydroxypropyl trimethyl ammonium chloride chitosan-loaded zeolite for cleaner dust consolidation: Enhanced mineralization and ammonium mitigation mechanisms - Ruoxi Li; Wen Nie; Linlin Zhang; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi (Process Safety and Environmental Protection, 2026)

In-situ synergistic mechanism of wetting and biomineralization in a polymeric surfactant-based microbial composite dust suppressant for dust control in open-pit mines - Ruoxi Li; Wen Nie; Linlin Zhang; Wenjin Niu; Qifan Tian; Jin Shi (Environmental Research, 2026)

DKK1 expression associates with tertiary lymphoid structure maturity in non-small cell lung cancer - Lin Ma; Linlin Yang; Junxu Wen; Fei Lu; Jinming Yu; Xiangjiao Meng (Apoptosis, 2026)

Parental exposure to ocean acidification impacts the larval development and transcriptome of the Pacific oyster Crassostrea gigas - Hailun Fu; Wen Teng; Shoudu Zhang; Zhangjie Peng; Jiulin Chan; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

The regulation of gut microbiota and urate lowering: A study on the mechanisms of action of probiotics and plant components - Zhihua Xing; Yue Xu; Wen Jiang; Mingyu Gao; Guanghuan Shen; Yingjie Liu; Na Ling; Linlin Cui (PharmaNutrition, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

A preliminary study on the community structure of culturable planktonic and attached bacteria in the harbor of Qingdao, China - Shide Ma; Linlin Zhang; Yimeng Zhang; Yu Tai; Wen Han; Jinfeng Yang; Xin Shi; Bochao Lu; Jizhou Duan (Acta Oceanologica Sinica, 2025)

A novel stochastic IDA-CSM based design framework of the externally-attached sub-system for seismic upgrading - Xu-Yang Cao; Dejian Shen; Kun Ji; Jiann-Wen Woody Ju; Linlin Xie (Bulletin of Earthquake Engineering, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

Copper Intake and Mortality Among Asthmatic Adults: A Cohort Study - Linlin Huang; Hegan Zhang; Rongjuan Zhuang; Jun Wen (Biological Trace Element Research, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

Fabrication, characterization, and antibacterial properties of sodium alginate/chito-oligosaccharide gel beads - Nan Wang; Jie Tian; Linlin Wang; Chen Song; Chengrong Wen; Yinghuan Fu; Shuang Song (Food Hydrocolloids, 2024)

Thermal interface materials with low modulus and high thermal conductivity by manipulating multi-branched PDMS network: The disentanglement and entanglement effect of dangling chain - Zhian Zhang; Zhibin Wen; Jiashuo Sheng; Chen Zeng; Jianfeng Fan; Linlin Ren; Xiaoliang Zeng; Rong Sun; Peng Chen (Chemical Engineering Journal, 2024)

Effects of chitosan and its oligosaccharide on gut microbiota and metabolites disturbed by excessive protein consumption in vivo and in vitro - Linlin Wang; Lilong Wang; Nan Wang; Chen Song; Chengrong Wen; Shuang Song (Food Bioscience, 2024)

Controllable synthesis of polyaspartic acid: Studying into the chain length effect for calcium scale inhibition - Meng-Long Zhang; Zheng Ruan; Yu Han; Zhi-Wei Cao; Linlin Zhao; Yuan-Qing Xu; Zhong-Yan Cao; Wen-Yan Shi; Ying Xu (Desalination, 2024)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Use of iron-loaded biochar to alleviate anammox performance inhibition under PFOA stress conditions: Integrated analysis of sludge characteristics and metagenomics - Linqin Tang; Chengyuan Su; Qing Wang; Linlin Cao; Yunchuan Xian; Shitong Wen; Yijie Zhou; Shu Gao (Science of The Total Environment, 2023)

Distinctive roles of land-use efficiency in sustainable development goals: An investigation of trade-offs and synergies in China - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu (Journal of Cleaner Production, 2023)

A decision-support system for recycling of residents’ waste plastics in China based on material flow analysis and life cycle assessment - Manzhi Liu; Jixin Wen; Linlin Zhang; Jixin Wu; Xiaotao Yang; Ying Qin; Yingjie Liu (Environmental Science and Pollution Research, 2022)

Neutralization Activity of Anti-drug Antibodies Against a Biotherapeutic Can Be Predicted from a Comprehensive Pharmacokinetics, Pharmacodynamics, and Anti-drug Antibody Data Analysis - Weifeng Xu; Brian Maas; Brad Roadcap; Aparna Swarup; Thomas Steinmetz; Linlin Luo; Marina Ichetovkin; Sandra Wood; Faye Vazvaei-Smith; Andrew Wen-Tseng Lee; Kalpit Vora; Roy Helmy (The AAPS Journal, 2022)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Reduced deep regional cerebral venous oxygen saturation in hemodialysis patients using quantitative susceptibility mapping - Chao Chai; Saifeng Liu; Linlin Fan; Lei Liu; Jinping Li; Chao Zuo; Tianyi Qian; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2018)

Phosphatidylinositol 3-phosphate, an essential lipid in Phytophthora sojae, enriches in the haustoria during infection - Linlin Chen; Wen Wang; Ying Hou; Yuren Wu; Honglian Li; Daolong Dou (Australasian Plant Pathology, 2016)

Bioavailability of riverine dissolved organic carbon and nitrogen in the Heilongjiang watershed of northeastern China - Jianhong Shi; Hongyang Cui; Liming Jia; Linlin Qiu; Yue Zhao; Zimin Wei; Junqiu Wu; Xin Wen (Environmental Monitoring and Assessment, 2016)

A gyrovirus infecting a sea bird - Linlin Li; Patricia A. Pesavento; Anne M. Gaynor; Rebecca S. Duerr; Tung Gia Phan; Wen Zhang; Xutao Deng; Eric Delwart (Archives of Virology, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Oxidative stress promotes d-GalN/LPS-induced acute hepatotoxicity by increasing glycogen synthase kinase 3β activity - Linlin Wei; Feng Ren; Xiangying Zhang; Tao Wen; Hongbo Shi; Sujun Zheng; Jing Zhang; Yu Chen; Yuanping Han; Zhongping Duan (Inflammation Research, 2014)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)